The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8ra03451f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of fluorinated graphene to study its gas sensitivity

Abstract: In this paper, fluorinated graphene was prepared from graphite fluoride by an improved Hummers method. The fluorinated graphene was characterized using an X-ray diffractometer (XRD), transmission electron microscope (TEM), atomic force microscope (AFM) and X-ray photoelectron spectrometer (XPS). Moreover, a gas sensitivity test was carried out. The results show that the fluorinated graphene is composed of about 5 layers prepared by utilising the improved Hummers method. The content of fluorine in fluorinated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…In addition, the weak peak at a binding energy of 291 eV is assigned to the C−F and/or Cl group. 62,63 In the F 1s region, the fitted peaks can be attributed to F−V, F x −Ti−C, and F−C bonds in both samples (Figure 7B and 8B). In the TiVCT x -HF sample the F−C bonds are centered at 686.5 eV and 688 eV, while in the TiVCT x -LiF/HCl sample they are located at binding energies of 688.5 eV and 693 eV.…”
Section: ■ Materials and Methodsmentioning
confidence: 93%
“…In addition, the weak peak at a binding energy of 291 eV is assigned to the C−F and/or Cl group. 62,63 In the F 1s region, the fitted peaks can be attributed to F−V, F x −Ti−C, and F−C bonds in both samples (Figure 7B and 8B). In the TiVCT x -HF sample the F−C bonds are centered at 686.5 eV and 688 eV, while in the TiVCT x -LiF/HCl sample they are located at binding energies of 688.5 eV and 693 eV.…”
Section: ■ Materials and Methodsmentioning
confidence: 93%
“…As a result, FG is regarded as a potential candidate in gas detection, storage, and separation. [98,[207][208][209][210][211][212] Liu et al displayed that FG showed a distinct color variation from white to dark yellow under the atmosphere of ammonia, which could be observed with naked eyes directly. The corresponding sensitivity reached a high value of 4.05% by PL measurement.…”
Section: Gas Detection Storage and Separationmentioning
confidence: 99%
“…Secondly, fluorinated graphene (FG) exhibits higher adsorption energies [147], higher sensitivity and better adsorption [148] of NH3 than the untreated one. FGs have also been reported to detect a wide variety of molecules other than NH3 [32], such as formaldehyde [149], dopamine [150], heavy metal ions [151] or humidity [152].…”
Section: Gas Sensingmentioning
confidence: 99%